Sintering, microstrusture and hardness of different alumina–zirconia composites - Calambas Pulgarin, Heydy Lorena (2014)
Two commercial 3 mol% yttria-partially stabilized zirconia powders, 0.3 wt% Al2O3-doped (Al-doped Y-PSZ) and without Al2O3 (Y-PSZ), were used to produce alumina (Al2O3)-zirconia (ZrO2) slip cast composites. The influence of the substitution of Al2O3 either by different Al-doped Y-PSZ contents or 50 vol% Y-PSZ on the sintering kinetic at the intermediate stage was investigated. In addition, the microstructure of Al2O3 and the different composites at temperatures in the range of 1100–1600 °C was studied and related to the sample hardness. An increase in the sintering rate was observed when Al-doped Y-PSZ increased from 22 to 50 vol% or when 50 vol% Y-PSZ was substituted by 50 vol% Al-doped Y-PSZ. 50 vol% ZrO2 was the most effective concentration to reduce the rate of Al2O3 grain growth in the final sintering stage; the Al2O3 grain growth began at lower temperatures and became greater with decreasing the Al-doped Y-PSZ content. On the contrary, the ZrO2 grain growth slightly increased with increasing the Al-doped Y-PSZ concentration. However, for 50 vol% Al-doped Y-PSZ a smaller ZrO2 grain size distribution compared with 50 vol% Y-PSZ could be achieved. As the average Al2O3 grain size of the sintered samples became greater than about 1 µm a markedly decrease in the hardness was found; this occurred at temperatures higher than 1400 °C and 1500 °C for Al2O3 and the composite with 10.5 vol% Al-doped Y-PSZ, respectively.